Creative digital language learning environment: A model to foster creative experiences for language learners - Hafizoah, Kassim; Asiah, Kassim; Nor Yazi, Khamis; Norhazwanie, Jatin; Aziz Hussin, Anealka; Uthayakumaran, Arulselvi (IEEE, 2023)
The exponential evolution of the 4IR technology has a profound influence on education including the teaching and learning of languages. Most studies in language learning looked at how technology can and should be explored to provide a better teaching and learning environment ultimately to help improve students’ language proficiency and competency. In contrast, how creativity can be fostered is rarely discussed in this digital context of language learning. Providing a creative learning opportunity in a technology-based language learning environment is therefore essential. We propose a creative digital language learning framework to foster creative experiences for language learners in order to assist the enhancement of their language ability and competency. Relevant parameters of the framework were explored in the literature, which were then validated by experts through interview protocols and by language learners via online questionnaire. Four main pillars of the model consist of the learning community, digital tools, instructional design and assessment. This model highlights the importance of creative learning experience for language learning in a digital environment. This model will serve as a guideline for design of instructional materials, and maximising the use of technology for augmenting and substantiating initiatives and aspiration to elevate learners’ language ability and competence as well as creative ability.